Consensus on the treatment of alopecia areata - Brazilian Society of Dermatology - Ramos, Paulo Muller [UNESP]; Anzai, Alessandra; Duque-Estrada, Bruna; Melo, Daniel Fernandes; Sternberg, Flavia; Nogueira Santos, Leopoldo Duailibe; Alves, Lorena Dourado; Mulinari-Brenner, Fabiane (Elsevier B.V., 2020)
Background: Alopecia areata is a highly frequent disease with an impact on quality of life and several treatment options with little clinical confirmatory evidence. Objective: To disseminate the recommendations of Brazilian dermatologists with expertise in the treatment of alopecia areata. Methods: Eight specialists with expertise in alopecia areata from different university centers were appointed by the Brazilian Society of Dermatology to reach a consensus on its treatment. Based on the adapted DELPHI methodology, the relevant elements were considered; then, an analysis of recent literature was carried out and the consensus was written down. Consensus on the management of alopecia areata was defined with the approval of at least 70% of the panel. Results/Conclusions: Intralesional injectable corticotherapy was considered the first optionfor localized disease in adults. In extensive cases with signs of activity, systemic cortico-steroid therapy should be considered and can be used together with immunosuppressants (corticosteroid-sparing agents). The use of an immunosensitizer (diphencyprone) is an option for stable long-term cases. Evaluation of side effects is as important as the rate of hair regrowth. (C) 2020 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Adrenal cortex hormones; Alopecia areata; Consensus; Methotrexate; Therapeutics